Nanocompartment-confined polymerization in living systems - Chen, Yun (2023)
Polymerization in living systems has become an effective strategy to regulate cell functions and behavior. However, the requirement of high concentrations of monomers, the existence of complicated intracorporal interferences, and the demand for extra external stimulations hinder their further biological applications. Herein, a nanocompartment-confined strategy that provides a confined and secluded environment for monomer enrichment and isolation is developed to achieve high polymerization efficiency, reduce the interference from external environment, and realize broad-spectrum polymerizations in living systems. For exogenous photopolymerization, the light-mediated free-radical polymerization of sodium 4-styrenesulfonate induces a 2.7-fold increase in the reaction rate with the protection of a confined environment. For endogenous hydrogen peroxide-responsive polymerization, p‑aminodiphenylamine hydrochloride embedded in a nanocompartment not only performs a 6.4-fold higher reaction rate than that of free monomers, but also activates an effective second near-infrared photoacoustic imaging-guided photothermal immunotherapy at tumor sites. This nanocompartment-confined strategy breaks the shackles of conventional polymerization, providing a universal platform for in vivo synthesis of polymers with diverse structures and functions.